2018
DOI: 10.2478/tour-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Gyms as an Example of Outdoor Recreation Activity in Urbanized Areas

Abstract: Abstract Outdoor gyms are becoming increasingly popular in the European cities. They are built in urban parks, in neighbourhoods (housing estates) and school sports grounds. Recently outdoor gyms are increasingly being built in non–urban recreation areas (such as beaches, lake promenades, forest parks). Among them there are gyms dedicated specifically to the elderly or disabled. The aim of the research is to analyze the use of outdoor gyms in Warsaw and selected surrounding set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…According to the different studies, using OGs represents only a supplementary activity and most people use OGs to supplement main activities and are active when they commute to the OGs (Chow, 2013(Chow, , 2017Ibiapina et al, 2017;Iepsen & Silva, 2015;Mathias et al, 2018;Mora, 2012;Mora et al,2017;Nałęcz et al, 2018;Pinheiro & Coelho Filho, 2017;Salin, Virtuoso, Noronha Nepomuceno, Weiers & Mazo, 2014;Silva, Fermino, Alberico & Reis, 2016Souza, Fermino, Rodriguez-Añez. & Reis, ,2014).…”
Section: Target Activity or Complementmentioning
confidence: 99%
See 4 more Smart Citations
“…According to the different studies, using OGs represents only a supplementary activity and most people use OGs to supplement main activities and are active when they commute to the OGs (Chow, 2013(Chow, , 2017Ibiapina et al, 2017;Iepsen & Silva, 2015;Mathias et al, 2018;Mora, 2012;Mora et al,2017;Nałęcz et al, 2018;Pinheiro & Coelho Filho, 2017;Salin, Virtuoso, Noronha Nepomuceno, Weiers & Mazo, 2014;Silva, Fermino, Alberico & Reis, 2016Souza, Fermino, Rodriguez-Añez. & Reis, ,2014).…”
Section: Target Activity or Complementmentioning
confidence: 99%
“…The percentage of time spent exercising was very low. In general, at most, users spend 15-20 minutes on 3-4 favourite machines (Bettencourt &Neves, 2016;Nałęcz et al, 2018) and some studies have observed that approximately half of the users only use one device and then leave. In general, no difference was found for total time of use based on gender.…”
Section: Time-duration Long-term Loyalty and Seasonalitymentioning
confidence: 99%
See 3 more Smart Citations